Arte 2000 en Castilla y León. - Castro Flórez, Fernando; Lucas, Juan José (Valladolid : Junta de Castilla y León, 1997)
Cuasante, José Maria ; Galindo, Florencio ; Mezquita, José Maria ; Concha, Felix de la ; Criado, Rufo ; Pisa, Agueda de la ; Calderon, Fernando Sánchez ; Toquero, Julio ; Reguera, Alberto ; Madrigal, Sofia ; Hernández, Luis Cruz ; Plaza, Juan Cruz ; Prieto, Javier Garcia ; Galero, Gonzalo Martin ; Rodrigo, Fernando ; de León, José ; Gómez, Maria ; Berlin, Dis ; Sanz, Eloisa ; Montoya, Isaac ; Navares, Paloma ; Banuelos, Alberto ; Isla, Miguel ; Giménez, Sara ; de Blas, Juan Ignacio
Arte 2000 en Castilla y León, Hospital de San Agustin - El Burgo de Osma, Soria, 07 - 09/1997
Spaans
boek